Nilai-Nilai Pendidikan Keluarga Dalam Ritual Phala Dara Sebagai Persyaratan Perkawinan Adat di Desa Brambang, Jembrana, Bali - Suwendra, I Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2024)
The Phala Dara ritual is unique, it only occurs in the Brambang Traditional Village, so it is very interesting to research. This research wants to find the meaning, procession and family education values ​​contained in the phala dara ritual. To achieve this goal, a qualitative research model was used, the method for determining research subjects was purposive and snowball sampling. Data was collected by in-depth interviews, involved observation and document recording. To dissect the existence/meaning of the phala dara ritual, the theory of existentialism is used, to dissect the phala dara ritual procession, religious and ritual theory is used, and to explore the values ​​of family education in the phala dara ritual, the educational theories of naturalism, emperism and convergence are used. After the data were collected, it was analyzed using categorization, taxonomic, cultural themes and focus group discussion techniques. The results of the research can be concluded as follows: (1) The meaning of the phala dara ritual is to make an agreement between the bride and groom to be loyal, share joys and sorrows together, work together harmoniously to form a prosperous and happy family witnessed by three witnesses, namely: Dewa saksi (Dewa witnesses), manusa saksi (human being witnesses), and bhuta saksi (Lower energy witnesses). (2) The phala dara ritual procession in marriage includes: (1) Arranging the piuning (offering with complete ceremonies to get a witness from God, (2) Making agreement between the bride and groom, the parents of the man and woman, the traditional leader (Manggala Desa Adat), and the Village Service as human witnesses, and (3) Offering for lower energy (bhuta kala) in the form of lower energy offering (Segehan Agung) to get bhuta witnesses.